PERAN GURU DALAM MELATIH KEMANDIRIAN ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA MELIAU - Atlanta, Tatiek; Ali, Muhamad; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe role of the teacher in training children's independence is very important so that children do not easily depend on others. This make the researcher want to examine the role of the teacher as a guide, motivator, facilitator, model or role model, and as an evaluator in training the independence of children aged 4-5 years in TK Negeri Pembina Meliau. This research was conducted using qualitative research methods. Data collection techniques used in this study were observation, interview, and documentation techniques with data collection tools in the form of observation guidelines, interview guidelines, field notes and documents. Data sources consisted of teachers who taught children aged 4-5 years and children aged 4 -5 years. After the data was collected, the researcher presents the data then draws the conclusions. From the results of the study it was found that the role of the teacher in training the independence of children aged 4-5 years namely the teacher guiding the child, providing opportunities for children to do their own activities, motivating children by giving enthusiasm and praise, providing children's facilities in learning activities, giving good models to imitated children and conduct assessments and evaluations of learning activities that have been carried out. The suggestion given is teachers are expected to provide affirmation to children who cannot do their own work and patience in guiding children, be creative in using or using interesting learning media in delivering learning activities.Â Key words: Early Childhood, Independence, Teacherâ€™s Role Â